An inquiry into the supply of and demand for pharmacy manpower, 1960-1977 - Newton, David Simpson
The study sought to examine the supply of and the demand for pharmacy manpower for the period 1960-1977. Utilizing National Association of Boards of Pharmacy data on resident licensed (active plus inactive) pharmacists and American Association of College of Pharmacy data on undergraduate degrees conferred, four projections of the supply of resident licensed pharmacy manpower were provided. These ranged from a low of 146,514 to a high of 159,555 (as of January 1, 1977). The projections employed a survey of forecast degrees expected to be conferred as well as linear least quare. Utilizing National Association of Boards of Pharmacy data on resident licensed (active only) pharmacists and U.S. Bureau of Census projections of population, three projections of the demand for resident active licensed pharmacy manpower were provided. These ranged from a low of 126,066 to 131,819 (as of January 1, 1977). The projections employed linear least square. In addition to the calculated projections for pharmacy manpower, a descriptive discussion of the more important factors which may affect pharmacy manpower was provided.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmacy Administration)--University of Mississippi, August 1971.
Keywords: Pharmacists -- Supply and demand